Eradication of Pulmonary Aspergillosis in an Adolescent Patient Undergoing Three Allogeneic Stem Cell Transplantations for Acute Lymphoblastic Leukemia - Michaela Döring; Angelika Zierl; Markus Mezger; Peter Lang; Rupert Handgretinger; Ingo Müller (Case Reports in Transplantation)
Systemic fungal infections are a major cause of infection-related mortality in patients with hematologic malignancies. This report addresses the case of an adolescent patient with acute lymphoblastic leukemia who underwent three allogeneic hematopoietic stem cell transplantations and developed pulmonary aspergillosis. Combination therapy with liposomal amphotericin B (L-AmB, 3 mg/kg bw/day) and caspofungin (CAS, 50 mg/day) during the first allogeneic hematopoietic stem cell transplantation (HSCT) improved the pulmonary situation. After shifting the antifungal combination therapy to oral voriconazole (2 × 200 mg/day) and CAS, a new pulmonal lesion occurred alongside the improvements in the existing pulmonary aspergillosis. An antifungal combination during a second HSCT with L-AmB (3 mg/kg bw/day) and CAS showed an improvement in the pulmonary aspergillosis. A combination therapy with CAS and L-AmB (1 mg/kg bw/day) during the third HSCT led once again to progress the pulmonary aspergillosis, after increasing the L-AMB to 3 mg/kg bw/day for recovery. The presented case provides an example of how, despite severe immunosuppression, a combination of antifungal drugs administered intravenously at therapeutic dosages may be more efficient than either intravenous monotherapy or combinations of intravenous and oral antifungals in selecting pediatric and adolescent patients with proven fungal infections.